E-Finance: What Factors Affect Financial Staff's Motivation to Utilize It? - Alam, M Dimar; Kusumadewi, Areta; Fitriyah, Laila (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2024)
The objective of this study is to investigate the factors that influence the intention of financial staff in the SKPDs of Malang City government to adopt e-finance. This study combines elements from the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) found in previous research. The survey method was utilized, with a sample of 155 respondents consisting of auditors employed in the financial department of Malang City's government. Data analysis was conducted using Partial Least Square (PLS) method. The study's results indicate that constructs like perceived ease of use, perceived usefulness, attitude, subjective norm, and perceived behavioral control have a positive impact on behavioral intention. Additionally, behavioral intention positively correlates with the actual behavior of financial staff using e-finance. The study underscores the significance for e-finance providers and management to consider perceived ease of use, perceived usefulness, attitude, subjective norm, perceived behavioral control, behavioral intention, and the actual behavior of users.